Argentine – Chili : Une si longue frontière - Sébastien Velut (Confins)
This paper explores South American regional integration from the vantage point of the very long boundary between Chile and Argentina and is material configurations. The drawing of this very long border, from international treaties to field, was a complex operation lasting more than one century. The limit is intersected by transcontinental itineraries that play a major role in the political projects of South American integration. Crossing devices, urban and road networks and exchanges define regional units.